2021
DOI: 10.3390/ijms221910872
|View full text |Cite
|
Sign up to set email alerts
|

The Lung Microbiome during Health and Disease

Abstract: Healthy human lungs have traditionally been considered to be a sterile organ. However, culture-independent molecular techniques have reported that large numbers of microbes coexist in the lung and airways. The lungs harbor diverse microbial composition that are undetected by previous approaches. Many studies have found significant differences in microbial composition between during health and respiratory disease. The lung microbiome is likely to not only influence susceptibility or causes of diseases but be af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
73
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 111 publications
(74 citation statements)
references
References 108 publications
0
73
0
1
Order By: Relevance
“…Given that A . suum also transiently colonizes the lungs, it would also be of interest in further studies to elucidate infection‐induced changes in bacterial taxa in the lung, given that the composition of the lung microbiome is increasingly recognized as playing an important role in both respiratory and perhaps also extrapulmonary health 73 …”
Section: Discussionmentioning
confidence: 99%
“…Given that A . suum also transiently colonizes the lungs, it would also be of interest in further studies to elucidate infection‐induced changes in bacterial taxa in the lung, given that the composition of the lung microbiome is increasingly recognized as playing an important role in both respiratory and perhaps also extrapulmonary health 73 …”
Section: Discussionmentioning
confidence: 99%
“…Culture-independent techniques changed the landscape of the lung microbiome scenario. Molecular-based techniques, such as 16S ribosomal (r) RNA and metagenomic sequencing, showed that lungs contain a large number of communities of microbes, even without clinical evidence of infection [15][16][17]. The rapid development of this field required clinical researchers to adopt a new language to describe lung microbial communities and their impact on lung health.…”
Section: Healthy Lung Microbiomementioning
confidence: 99%
“…Besides, butyrate-producing organisms from the Clostridium cluster XIVa and a reduction in anti-inflammatory organisms such as F. prausnitzii and Akkermansia muciniphila have also been reported [ 35 ]. Lung dysbiosis in patients with chronic respiratory diseases compared to the general population has been observed and reported [ [36] , [37] , [38] , [39] ]. Current evidence has highlighted that gut dysbiosis has an inflammatory effect on the joints, liver, or brain, influencing disease progression through the gut-joint axis [ 40 ], gut-liver axis [ 41 ], and gut-brain axis [ 42 ], respectively.…”
Section: Main Textmentioning
confidence: 99%